"Unflushables": Establishing a global agenda for action on everyday practices associated with sewer blockages, water quality, and plastic pollution. (26th May 2020) - Alda‐Vidal, Cecilia; Browne, Alison L.; Hoolohan, Claire
Abstract: The disposal of unflushable products via the toilet is an enduring problem and increasing contributor to environmental and infrastructural challenges such as fatbergs, water quality and plastic pollution. Rising scientific and public interest in "throw‐away" cultures, and renewed government pressure for water and sewerage companies to act as custodians of water resources, raises questions about how and why impactful disposal practices occur and what might be done to change them. To date there has been little systematic research on unflushable products, and little is known about the routines and practices through which unflushable products find their way into wastewater systems. This paper reviews social science research including historical, sociological, and anthropological studies of cleanliness and hygiene, as well as sociotechnical approaches to the study of household practices and infrastructures to understand the challenges of unflushables. Based on this research, the paper offers a new conceptualization of the unflushables challenge. We argue that unflushables are a distributed problem, one that is not the direct consequence of either individual behavior, product design or infrastructural decline, but the outcome of myriad social, cultural and material developments in society. These include diversity in "flushing" cultures, gendered expectations in cleanliness practices; the evolution of conventions around cleanliness and hygiene; infrastructural imaginaries and expectations; and political dimensions of infrastructural development and maintenance. We demonstrate how social science research is essential in defining a new global research agenda on unflushables that further aids the design of new intervention and policy pathways. This article is categorized under: Engineering Water > Sustainable Engineering of Water Science of Water > Water Quality Abstract : Hygiene waste in sewers: Components of the sociomaterial practices of disposal contributing to plastic waste in sewers and water systems.